2018
DOI: 10.7554/elife.36158
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione de novo synthesis but not recycling process coordinates with glutamine catabolism to control redox homeostasis and directs murine T cell differentiation

Abstract: Upon antigen stimulation, T lymphocytes undergo dramatic changes in metabolism to fulfill the bioenergetic, biosynthetic and redox demands of proliferation and differentiation. Glutathione (GSH) plays an essential role in controlling redox balance and cell fate. While GSH can be recycled from Glutathione disulfide (GSSG), the inhibition of this recycling pathway does not impact GSH content and murine T cell fate. By contrast, the inhibition of the de novo synthesis of GSH, by deleting either the catalytic (Gcl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
109
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 148 publications
(114 citation statements)
references
References 119 publications
5
109
0
Order By: Relevance
“…The balance between ROS generation and antioxidant capacity is necessary to ensures physiological levels of intracellular ROS and T cell-mediated immune response. Accordingly, excessive ROS generation in T cells will destroy the intracellular redox balance and leads to metabolism disorder and immune response dysfunction [30,31]. Here, we also observed markedly raised ROS level and decreased antioxidant enzyme activity of SOD, CAT and GSH-Px in the D-gal-treated group.…”
Section: Discussionsupporting
confidence: 59%
“…The balance between ROS generation and antioxidant capacity is necessary to ensures physiological levels of intracellular ROS and T cell-mediated immune response. Accordingly, excessive ROS generation in T cells will destroy the intracellular redox balance and leads to metabolism disorder and immune response dysfunction [30,31]. Here, we also observed markedly raised ROS level and decreased antioxidant enzyme activity of SOD, CAT and GSH-Px in the D-gal-treated group.…”
Section: Discussionsupporting
confidence: 59%
“…17,66,[129][130][131][132][133][134][135] Another consequence of increased mitochondrial biogenesis is augmented serine-and folate-dependent one-carbon metabolism, which regulates the generation of the methyl-donor S-adenosylmethionine (SAM), as well as glutathione and nucleotides important for T cell activation. 124,[136][137][138][139][140] In T cells, the upregulation of one-carbon metabolism-associated enzymes requires mTORC1 activation, 66 which may be mediated by the mTORC1-dependent activation of ATF4. 141 In summary, mTOR activity coordinates transcriptional and post-transcriptional programming to mediate anabolic metabolism for control of T cell responses.…”
Section: Metabolic and Immunological Inputs For Mtorc1mentioning
confidence: 99%
“…GSH is an important endogenous antioxidant that has a prominent contribution against oxidative stress (Hartmann et al, 2017). Lian et al (2018) showed that glutamine improves the oxidative stress response induced by myocardial I/R by enhancing GSH synthesis. The study reported that the glutamine metabolism in rat heart is inhibited by I/R, and pretreatment with glutamine reduces I/R injury and MI area with I/R injury.…”
Section: Glutamine Improves Myocardial Ischemia-reperfusion Injury Wimentioning
confidence: 99%